Prefrontal brain function in patients with chronic insomnia disorder: A pilot functional near-infrared spectroscopy study - Gong, Haiyan; Sun, Hui; Ma, Yeyang; Tan, Yaling; Cui, Minglong; Luo, Ming; Chen, Yuhui (Frontiers in Neurology, 2022)
Background： In this paper, functional near-infrared spectroscopy (fNIRS) was used to study the relationship between drug treatment and the changes in prefrontal cortex (PFC) function patterns in patients with chronic insomnia disorder. Methods： All subjects were assessed using the Pittsburgh Sleep Quality Index (PSQI), Hamilton Depression Scale (HAMD), Hamilton Anxiety Scale (HAMA), and fNIRS. The fNIRS assessment comprised two parts: the Verbal Fluency Test (VFT) task state and the resting state, which assessed the differences in prefrontal activation and functional connectivity, respectively. Results： Thirty CID（Chronic Insomnia Disorder） patients and 15 healthy peers completed the study. During the VFT task, a significantly lower PFC activation was observed in patients with insomnia compared to the control group (P<0.05). However, the PFC activation in patients taking medication was higher than in patients who did not receive medication. Functional connectivity analysis showed a weaker mean PFC channel connectivity strength in CID patients who did not receive drug treatment. Drug treatment resulted in enhanced functional connectivity of the prefrontal lobe, especially the dlPFC and frontal poles. Conclusions： A weak prefrontal cortex response was detected in patients with CID when performing the VFT task, which could be enhanced by taking hypnotics. The weakened right prefrontal lobe network may play a role in the development of CID. fNIRS may serve as a potential tool to assess sleep status and guide drug therapy.